2021
DOI: 10.1097/fpc.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation at the sulfotransferase 1a1 gene is associated with its hepatic expression in normal aging

Abstract: Objectives Phase II drug metabolism is poorly studied in advanced age and older adults may exhibit significant variability in their expression of phase II enzymes. We hypothesized that age-related changes to epigenetic regulation of genes involved in phase II drug metabolism may contribute to these effects. MethodsWe examined published epigenome-wide studies of human blood and identified the SULT1A1 and UGT1A6 genes as the top loci showing epigenetic changes with age. To assess possible functional alterations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In addition, UGT1A6 and UGT1A9 genes encode for two UGTs that are altered in the elderly. UGT1A6 expression shows altered epigenetic regulation with aging in human blood samples (Kronfol et al, 2021), while UGT1A9 expression has been shown to be decreased in the aged mouse liver (Warren et al, 2018). By performing a functional enrichment analysis, we found alterations in drug and estrogen metabolism and the modulation of the immune response in UDSCs from elderly female adults.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, UGT1A6 and UGT1A9 genes encode for two UGTs that are altered in the elderly. UGT1A6 expression shows altered epigenetic regulation with aging in human blood samples (Kronfol et al, 2021), while UGT1A9 expression has been shown to be decreased in the aged mouse liver (Warren et al, 2018). By performing a functional enrichment analysis, we found alterations in drug and estrogen metabolism and the modulation of the immune response in UDSCs from elderly female adults.…”
Section: Discussionmentioning
confidence: 91%
“…SULT1A1, an important phase-II xenobiotic metabolizing enzyme, is highly expressed in the liver and mediates the sulfonation of steroids, drugs, and carcinogens . SULT1A1 assumes a major role in the chemical and functional homeostasis of substrate chemicals and hormones. Owing to its functions in the metabolism of xenobiotics and endogenous hormones, SULT1A1 and its regulation are implicated in the pathophysiology of liver disease , and cancer. , Hence, we decided to choose this protein for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…As a phase-II metabolic enzyme, SULT1A1 assumes a major role in chemical and functional homeostasis by adding sulfate groups to hydroxyl functionalities in substrate chemicals and hormones, thereby improving their solubilities and promoting their excretion. 27−29 Due to its function in the metabolism of xenobiotics, SULT1A1 and its aberrant regulation are implicated in the pathophysiology of liver disease 30,31 and cancer. 32,33 Therefore, the regulatory role of Aha1 in the expression level of SULT1A1 protein that we uncovered herein may provide an important basis for developing approaches toward therapeutic interventions of these diseases.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic processes profoundly affect the expression of genes involved in xenobiotic metabolism and transport [9,10] and upregulation of genes involved in xenobiotic detoxification is a common mechanism of increased longevity across phyla [11,12]. Recent studies in laboratory mice suggest that epigenetic aging may substantially alter the hepatic expression and function of some ADME genes [13,14]. However, comprehensive genome-wide studies of epigenetic aging effects on ADME genes have been limited.…”
Section: Introductionmentioning
confidence: 99%